Psychoeducational intervention regarding parental roles in the process of cancer - Rodríguez-Morera, Anna; Fuentes Sanmartín., Sònia; Lleras De Frutos, María (Psicooncología, 2025)
Introduction: family involvement in the care of individuals with cancer is a central objective of oncology teams. Within this framework, supporting patients’ children is considered essential. In many cultures, including our own, children and adolescents are often overprotected from receiving distressing information, from exposure to illness and death, and, more broadly, from emotionally impactful experiences. This tendency may inadvertently undermine their right to autonomy and contribute to increased vulnerability within the family context. Methodology: a review was conducted of existing studies and psychoeducational support materials designed for parents with cancer and their minor children. This review is informed by clinical experience in applying these resources in practice. Intervention Proposal: To facilitate access to appropriate support, a set of general recommendations and four age-specific psychoeducational guides were developed. These materials are designed to be user-friendly and culturally adapted to the needs of our population. Discussion: Preventive interventions can mitigate the impact of risk factors associated with parental cancer and help foster resilience by strengthening protective factors. Providing written informational support in the form of a brochure for parents with cancer constitutes a preventive psycho-oncological strategy implemented at the Catalan Institute of Oncology.